Annual Plan 1994-95 Vol. I General Profile - Planning Commission (Planning Commission, 1994)
A brief description of the economic situation in the state, the land use pattern, and the performance of the state in the more recent past in some significant socio-economic areas has been presented in this chapter is divided into three parts. Part-I, it is a description of the economic situation, Part-II gives the existing as well as the desirable land use pattern in the State, and part-III is a review of the past performance. Part-I Economic Situation Before describing the economic situation of the State in some greater details, it might be useful to give here an over-view of State’s economic by describing its some most salient features as stated below : The dominant role of agriculture in the economy and in determining its rate of growth
Government of Uttar Pradesh State Planning Commission